CHARACTERISTICS OF IRON EXCHANGE IN TUBERCULOSIS (Multidisciplinary Journal of Science and Technology, 2024)
Mycobacterium tuberculosis requires iron for normal growth, but is subject to metal ion limitation due to its low solubility at biological pH and iron retention by mammalian hosts. The pathogen expresses a specific siderophore for Fe 3+ to chelate the metal ion from insoluble iron and the proteins transferrin, lactoferrin, and ferritin. Siderophore-mediated iron uptake is essential for survival in tuberculosis disease, as knockout mutants defective in siderophore synthesis or uptake failed to survive in iron-deficient environments and in host macrophages. However, since excess iron is toxic due to its catalytic role in the generation of free radicals, iron uptake must be regulated to maintain optimal intracellular iron levels. The main objective of this review is to provide a comprehensive overview of iron homeostasis in M. tuberculosis, discussed in the context of mycobactin biosynthesis, iron transport across the mycobacterial cell envelope, and storage of excess iron.